1993
DOI: 10.1016/0014-5793(93)80489-h
|View full text |Cite
|
Sign up to set email alerts
|

Assignment of the backbone 1H and 15N NMR resonances and secondary structure characterization of barstar

Abstract: Barstar, a polypeptide inhibitor of ribonucleases, has been studied by 2D and 3D NMR techniques using uniformly '5N-labeled protein. Backbone ("NH-C,H-CflH) resonances were assigned for all but 5 of the 89 residues. Dihedral angle and deuterium exchange studies were used in conjunction with medium range inter-proton NOES to characterize the secondary structure of barstar. The protein is composed of four a-helices and three short stretches of extended strand. By further analysis of the NOE data three of the hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 22 publications
1
29
0
1
Order By: Relevance
“…The positive entropic contribution has previously been suggested to be due to both an increase in flexibility of the molecule and a release of water molecules upon complex formation (12). Earlier measurements of hydrogen exchange rates by NMR (22,42,43) have suggested that free barstar is a flexible molecule. The C82A structure does not show any evidence for increased flexibility of barstar upon binding to barnase.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The positive entropic contribution has previously been suggested to be due to both an increase in flexibility of the molecule and a release of water molecules upon complex formation (12). Earlier measurements of hydrogen exchange rates by NMR (22,42,43) have suggested that free barstar is a flexible molecule. The C82A structure does not show any evidence for increased flexibility of barstar upon binding to barnase.…”
Section: Resultsmentioning
confidence: 98%
“…The average side-chain rmsd for a similar comparison yields values of 1.06 and 1.11 Å, respectively. The main-chain residues of barstar (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)) that lie at the binding interface with barnase do not show significant deviations in comparison to the structure in the complex, except for Gly 43 ( Figures 2B, 3A, and 4A). Taking into consideration the resolution of this structure as well as the quality of the electron density map, the side-chain residues in the binding site which show significant changes in C82A when compared to 1BRS are Y29, D35, and D39 ( Figure 4A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, for His-2f3, no amide *The sequences of the chimeric proteins are as described in Table 1 with appended tags MRGSHHHHGSR (N terminus) and AQAEA (C terminus). † The conformational stability ⌬G at a temperature T was calculated by using the Gibbs-Helmholtz equation ⌬G(T) ϭ ⌬H m(1 Ϫ T͞Tm) Ϫ ⌬Cp [(Tm Ϫ T) ϩ ln(T͞T m)], while inferring the midpoint of thermal unfolding (Tm) and the enthalpy change for unfolding (⌬H m) at the Tm from the denaturation curve (30) and assuming for ⌬C p (the difference in heat capacity between unfolded and folded conformation at constant pressure) a value of 12 cal per residue (40). ‡ The His-Csp͞2 protein, which comprises the N-terminal half of CspA (LQSGK-MTGIV KWFNADKGFG FITPDDGSKD VFVHFSAW) plus the terminal tags, was found in neither the soluble nor the insoluble fraction of the cytoplasm and is presumed to have been degraded within the cell.…”
Section: Resultsmentioning
confidence: 99%
“…For selections, 10 10 colony-forming units (cfu) of phage were treated with 200 nM trypsin (specific for Arg or Lys in the P 1 position) and 384 nM thermolysin (specific for aliphatic side chains in the P 1Ј position) in TBS-Ca buffer (25 mM Tris⅐HCl͞137 mM NaCl͞1 mM CaCl 2 , pH 7.4) for 10 min at 10°C. After proteolysis, phage was captured for 1 h with biotinylated C40A,C82A double-mutant of barstar (29,30) immobilized on streptavidin-coated microtiter plate wells in 3% Marvel in PBS. Wells were washed 20 times with PBS (and once with 50 mM DTT in PBS for 5 min to elute phage containing proteolyzed p3 fusions held together solely by disulfide bridges).…”
Section: Methodsmentioning
confidence: 99%